Cranial polyneuropathy and triparesis due to mononeuritis multiplex in a case of scrub typhus - Das, Sayonee; Islam, Ramiz; Biswas, Parvez Shahide; Munsi, Kausik; Basu, Sagar (International Journal of Advances in Medicine, 2021)
Scrub typhus with neurological manifestations are often described. We present here unusual neurological manifestations in a patient with Scrub typhus. A 49 years old male presented with continued fever for the last 12 days along with headache and myalgia. He had left sided oculomotor nerve palsy along with palatal palsy and triparesis (except left upper limb) of lower motor neurone type. Electro-diagnostic studies showed asymmetric axonal sensorimotor neuropathies of multiple nerves in paretic limbs, suggestive of mononeuritis multiplex. Scrub typhus was diagnosed by the presence of IgM antibody in serum. He responded well with doxycycline therapy. This type of neurological presentation is extremely rare in scrub typhus and possibly has not been described earlier to the best of our knowledge.